The appraisal of slope management in forecasting failure mechanism [electronic resource] - 456309 Wong, Chee Kan; Fakulti Kejuruteraan Awam (2005)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2005